(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2012)
By the 1960s, the Indian bankingindustry has become an important tool to facilitate the development of theIndian economy. At the same time, it has emerged as a large employer, and adebate has ensued about the possibility to nationalize the banking industry.Indira Gandhi, the-then Prime Minister of India expressed the intention of theGOI in the annual conference of the All India Congress Meeting in a paperentitled "Stray thoughts on Bank Nationalization." The paper wasreceived with positive enthusiasm. Thereafter, her move was swift andsudden, and the GOI issued an ordinance and nationalized the 14 largestcommercial banks with effect from the midnight of July 19, 1969. JayaprakashNarayan, a national leader of India, described the step as a "masterstrokeof political sagacity." Within two weeks of the issue of the ordinance, theParliament passed the Banking Companies (Acquisition and Transfer ofUndertaking) Bill, and it received the presidential approval on 9th August,1969. A second dose of nationalization of6 more commercial banks followed in 1980. The stated reason for the nationalizationwas to give the government more control of credit delivery. With the seconddose of nationalization, the GOI controlled around 91% of the banking businessof India.